The Fabulous Promise and Practical Need for the Humanities in the Twenty-First Century - Riordan, Liam (Maine Policy Review, 2015)
Guest editor Liam Riordan in this overview article explores the relationship between the humanities and policy in general terms, identifying the recurring themes in the other articles in this special issue of Maine Policy Review. He contends that the humanities offer fabulous promise to enrich the quality of civic life in Maine and that this promise is firmly rooted in how the humanities address our practical need for meaningful human experiences.